The sustainablility of traditional Chinese villages: a perspective from the production of space - Song, Mengru; Kim, Ji-Eun (Frontiers in Environmental Science, 2025)
As custodians of intangible cultural heritage and ecological knowledge systems, Chinese traditional villages face dual challenges, namely, rapidnew urbanization and the commodification of capital-driven spaces. Thus, the sustainability crisis within their living environments has become increasingly prominent. This study reviews Henri Lefebvre’s theory of the production of space and the features of traditional villages through a literature review. It identifies six sustainable characteristics of traditional villages, grounded in the theory of the production of space. Case studies of four distinct traditional villages (Hongcun, Anhui; Yazhe Zaozu, Sichuan; Tianluokeng, Fujian; Dingcun, Shanxi) — representing diverse types and geographical contexts—were conducted to validate these characteristics. The results indicate the following: First, the sustainability of the living environment in traditional villages manifests not only in the persistence of physical spaces, but more fundamentally in the maintenance of social bonds and spiritual culture. Second, the holders of rights in traditional villages vary across regions and village types. Third, the sustainability of the living environments typically exhibits distinct local characteristics, rich experiential narratives, strong collective practices, considerable resilience, significant cultural symbolism, and close interconnectivity. These findings extend the applicability of the production of space in examining the sustainability of rural living environments, offering valuable theoretical insights and practical strategies for the conservation and sustainable development of Chinese traditional villages.